Optical Properties of Indium-Doped ZnO Nano-Films Prepared by Spray Pyrolysis and Hydrothermal Synthesis - Liu, Ruxi; Zhang, Zhong; Huang, Jinzhao; Li, Honglin (Asian Journal of Chemistry, 2013)
Zinc oxide and indium-doped ZnO nano-films are prepared by two-step method on the quartz glass substrate. The growth orientation along c-axis of ZnO nano rods is changed by indium doping and with the increase of indium proportion, the orientation along (101) plane increase. The structure changes from prism-like nano rods to nanofilms due to the different indium proportion. New energy levels are introduce into ZnO causing a blue shift in the green emission region and more oxygen vacancies that results a better blue emission at 404 nm.